Improving Heat Transfer Enables Durable Perovskite Solar Cells. Issue 24 (6th May 2022) - Yang, Ning; Pei, Fengtao; Dou, Jie; Zhao, Yizhou; Huang, Zijian; Ma, Yue; Ma, Sai; Wang, Chenyue; Zhang, Xiao; Wang, Hao; Zhu, Cheng; Bai, Yang; et al.
Abstract: Special attention should be devoted to the thermal stability of hybrid perovskite solar cells (PSCs), because they are often operated at elevated temperatures. However, effective strategies are lacking for manipulation of heat flow in PSCs to improve their thermal stability. Here, a holistic solution is reported for the rapid removal of dissipated heat within the absorber by introducing hexagonal boron nitride (h‐BN) inside and radiator fin outside of the device. This strategy significantly improves the thermal conductivity of perovskite and speeds up the heat transfer of device, which effectively reduces the cell temperature under illumination of simulated AM 1.5G standard spectrum by ≈6.5 °C. Regardless of device configurations, the corresponding PSCs exhibit prolonged lifetimes aged at different temperatures, continuously operated under white light‐emitting diode (LED) lamp or full‐spectrum illumination. Of particular note, the optimized h‐BN/Cu device with n–i–p structure keeps 88% and 93% of its initial PCE after 1776 h of 85 °C thermal aging and 2451 h of maximum power point (MPP) tracking, respectively, and the device with p–i–n structure maintains 96% and 92% of its original PCE after 1704 h of 85 °C thermal aging and 2164 h of MPP tracking. Abstract : A holistic solution is proposed that is generally applicable for perovskite solar cells with either n–i–p or p–i–n structures to improve their heat transfer by introducing hexagonal boron nitride inside of absorber and the radiator fin outside of device. The optimized device retains 93% of its initial efficiency after 2451 h of maximum power point tracking.